Return to work rate of individuals after cardiac rehabilitation and the demographic and impairment factors that influence return to work in the Western Cape, South Africa [version 2; peer review: 1 approved, 2 approved with reservations] - Zakeera Ganie; Shaheed Soeker; Anthea Rhoda (F1000Research, 2023)
Background Cardiovascular disease (CVD) commonly affects individuals within the working age group, often resulting in unemployment, particularly in low- to middle-income countries. The purpose of the study was to determine the return to work (RTW) rate of individuals with CVD after cardiac rehabilitation (CR) and the impact of impairment and socio-demographics on the individual’s ability to (RTW). Methods A cross-sectional survey, namely the Work Rehabilitation Questionnaire (WORQ) was used to gather the information. The IBM SPSS software (version 25) was used to manage the statistical analysis. Individuals who completed a CR program between the ages of 18 and 64 years made up a sample of 63 research participants. Results The RTW rate reported that only 30 (47.6%) of the participants successfully RTW after CR and 33 (52.4%) of participants did not RTW. The results also indicated that the older the individual and the higher the degree of impairment experienced, the less likely RTW would occur. Conclusion Factors such as the age and level of functional impairment of the individual with CVD must be addressed more aggressively in CR programs, particularly if the goal of the individual with CVD is to RTW.